Hydrodynamic characteristics in aerobic biofilm reactor treating high-strength trade effluent - Chua, H.; Yu, P. H. F. (Applied biochemistry and biotechnology, 1997)
Four 3-L aerobic biofilm reactors (ABRI, 2, 3, and 4) treating a high-strength food-processing waste water (10 g chemical oxygen demand [COD]/L) were subject to reactor liquor recirculation rates of 1, 3,15, and 30 L/h, respectively. Treatment performance in terms of COD removal rates of ABRI, 2, and 3 were similar at hydraulic loads of 2.0 g COD/L/d and below. At higher organic loads, ABR3 could achieve a COD removal rate that was over two times higher than that of ABRI and 2. ABR3 could be operated at a maximum organic load that was two times higher than that of ABRI and 2. ABR4 experienced a biofilm sloughing from the packing medium at the beginning of operation. Tracer studies showed that recirculation rate of 1 L/h resulted in a plug-flow pattern in the packed bed of the reactor. On the other hand, recirculation rate of 15 L/h, which was equivalent to recirculating the reactor liquor five times per hour, provided effective mixing in the packed bed. Superior performance of ABR3 was attributed to the effective recirculation of reactor liquor, which diluted and distributed the influent, particularly the oil and grease components.